Perioperative and Long-term Outcomes of Endovascular Treatment for Subclavian Artery Disease From a Large Multicenter Registry. (August 2015) - Soga, Yoshimitsu; Tomoi, Yusuke; Fujihara, Masahiko; Okazaki, Shinya; Yamauchi, Yasutaka; Shintani, Yoshiaki; Suzuki, Kenji; ,
Purpose: To investigate the perioperative and long-term outcomes of endovascular therapy (EVT) for subclavian artery disease in a large-scale multicenter study.Methods: The study analyzed the outcomes from a multicenter retrospective registry (SubClavian Artery disease treated with endovascuLar therapy; muLticenter retrOsPective registry: SCALLOP) of 718 consecutive patients with upper extremity artery disease who underwent EVT between January 2003 and December 2012 at 37 Japanese cardiovascular centers. Of the 718 patients enrolled in the registry, 162 patients were excluded, leaving 553 patients (mean 70±7 years, range 41–91; 405 men) who underwent primary EVT for de novo subclavian artery disease (560 arms).Results: Procedure success was achieved in 96.8% (100% for stenoses, 91% for total occlusions). The perioperative complication rate was 9.2%. Stroke was found in 1.8%, with ipsilateral posterior infarction accounting for 0.9%. The 30-day mortality was 0.7%. The mean follow-up was 39±24 months. Primary patency estimates were 90.6%±1.3%, 83.4%±1.8%, and 80.5%±2.2% at 1, 3, and 5 years, respectively. There was no significant difference in primary patency between stenotic and occlusive lesions. Secondary patency estimates were 99.2%±0.4%, 98.2%±0.6%, and 97.7%±0.8% at 1, 3, and 5 years, respectively. The respective overall survival rates were 94.6%±1.0%, 86.8%±1.7%, and 79.0%±2.4%. There were 86 deaths during follow-up, of which half were due to cardiovascular causes. On multivariate analysis, critical hand ischemia (hazard ratio [HR] 4.6, 95% CI 2.06 to 10.2, p<0.001), cerebrovascular disease (HR 1.9, 95% CI 1.14 to 3.06, p=0.01), current smoking (HR 1.8, 95% 1.14 to 2.79, p=0.01), and lesion length (in 1-cm increments; HR 1.02, 95% CI 1.00 to 1.04, p=0.03) were negative independent predictors of primary patency, while IVUS use (HR 0.6, 95% CI 0.30 to 0.96, p=0.04) was a positive predictor of primary patency.Conclusion: Primary angioplasty/stenting for subclavian artery disease afforded acceptable outcomes in terms of perioperative complications and long-term patency.